Ammonium fractions and their kinetic release in salt-affected soils, Northeast Thailand - Chaiyapo, Peangdin; Thanachit, Suphicha; Anusontpornperm, Somchai; Kheoruenromme, Irb Kheoruenromme (Agriculture and Natural Resources, 2024)
Importance of the work: Release and fractions of ammonium (NH4+-N) as differently influenced by salinity and sodicity are crucial for rice production. Objectives: To investigate NH4+-N fractions and their kinetic release in salt-affected soils with different salinity and sodicity levels. Materials and Methods: The soil N status was studied in seven salt-affected soils using the chemical sequential fractionation of soil NH4+-N and the kinetics of NH4+-N release based on successive extractions with 0.01 M CaCl2 solution. In addition, spiked soil samples with the addition of 1,000 mg NH4+/kg were prepared for the kinetic release of recently fixed NH4+-N. Results: The non-exchangeable NH4+-N fraction was dominant in the tested native soils, accounting for 60.5–89.0% of the total concentration, while the exchangeable and water-soluble NH4+-N fractions were similarly lower (1.71–14.86 and 1.29–9.65 mg/kg, respectively). The NH4+-N release was in the range 6.2–20.3% of the total N in the soils. When NH4+-N was added, 10.9–36.7% of the NH4+-N was fixed. The kinetics of NH4+-N release for both the native and the spiked soil samples were biphasic and best described using Elovich models. The release rate constants of NH4+-N were positively governed by the total N, organic matter, silt and the exchangeable and non-exchangeable NH4+-N contents. In contrast, soil pH and all sodicity-related parameters had strongly negative correlations with the NH+4 release rate, with exchangeable Na having the highest correlation among the sodicity-related parameters. On the other hand, salinity was not correlated with the NH4+-N release rate. Main finding: Sodicity, particularly exchangeable Na, appeared more responsible than salinity for the low rate of NH4+-N release in these salt-affected soils.